2017
DOI: 10.1186/s12957-017-1240-2
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant treatment of pancreatic adenocarcinoma: a systematic review and meta-analysis of 5520 patients

Abstract: BackgroundRecent years have seen standardization of the anatomic definitions of pancreatic adenocarcinoma, and increasing utilization of neoadjuvant therapy (NAT). The aim of the current review was to summarize the evidence for NAT in pancreatic adenocarcinoma since 2009, when consensus criteria for resectable (R), borderline resectable (BR), and locally advanced (LA) disease were endorsed.MethodsPubMed search was undertaken along with extensive backward search of the references of published articles to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 120 publications
4
115
2
1
Order By: Relevance
“…15,20 A recent systematic review and meta-analysis on patients with 935 BRPC reported the rate of exploration in these patients to be 77% and the rate of resectability to be 69%. 21 Katz et al in their initial report of the ALLIANCE trial A021101 reported the rate of resectability in BRPC to be 68% following neoadjuvant treatment (15/22). 22 Similar to our findings, the PREOPANC-1 trial reported a rate of resection of 72% in BRPC patients who underwent straight to surgery as compared to 62% in patients who received neoadjuvant therapy prior to resection.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 A recent systematic review and meta-analysis on patients with 935 BRPC reported the rate of exploration in these patients to be 77% and the rate of resectability to be 69%. 21 Katz et al in their initial report of the ALLIANCE trial A021101 reported the rate of resectability in BRPC to be 68% following neoadjuvant treatment (15/22). 22 Similar to our findings, the PREOPANC-1 trial reported a rate of resection of 72% in BRPC patients who underwent straight to surgery as compared to 62% in patients who received neoadjuvant therapy prior to resection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to altering patient selection for surgery, high neoadjuvant utilization may contribute to improved outcomes [38]. Therefore, the recent literature on neoadjuvant therapy in PDAC demonstrates improved outcomes after neoadjuvant therapy compared to those historically associated with the surgery-first approach for PDAC reported in a systematic review and meta-analysis of 5,520 patients [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rates of resection after neoadjuvant therapy were 76%, 69% and 26% for resectable PDAC, bordeline PDAC and locally advanced PDAC, respectively (70). The median overall survival time after neoadjuvant therapy and pancreatectomy was 30 months for resectable PDAC, 27.4 months for borderline PDAC and 18.7 months for locally advanced PDAC (70). It is worth to mention that a limited number of patients in the analyzed studies included FOLFIRINOX regimens (70).…”
Section: Neoadjuvant Therapies In Pdacmentioning
confidence: 98%
“…A recent systematic review and meta-analysis has shown that neoadjuvant therapy is associated with a radiological response (i.e., disease control) in 88% of the patients with resectable PDAC and in 77% of patients with borderline and locally advanced PDAC (70). Furthermore, the rates of resection after neoadjuvant therapy were 76%, 69% and 26% for resectable PDAC, bordeline PDAC and locally advanced PDAC, respectively (70).…”
Section: Neoadjuvant Therapies In Pdacmentioning
confidence: 99%
See 1 more Smart Citation